Volatile profile and its application on species authentication of meat-based food - Indrasti, Dias; Ramadhina, Siti Hanifah Rifan (Journal of Halal Science and Research, 2025)
Meat and meat-based food produces a certain composition of volatile compounds, which can be used to identify its origin and, consequently, for food authentication. Numerous studies have explored the application of volatile compounds in identifying meat-based food using volatilomics, an emerging analytical technique. This review focuses on the volatile compound profiles, the factors influencing their production, method of extraction and detection, and their application in meat and meat-based products, with a brief discussion on their potential use for Halal authentication. The major volatile compounds associated with meat aromas include aldehydes, ketones, and alcohols, with variation in composition among different types of meat, though no definite pattern has been identified. Most of these volatile compounds are byproducts of the Maillard reaction, Strecker degradation, or interaction of both, as well as thiamine degradation. Head space-solid phase microextraction (HS-SPME) is meat's standard volatile compounds extraction method due to its convenience, solvent-free process, high sensitivity, and practicality. Gas chromatography-mass spectrometry (GC-MS) is the primary analytical technique for detecting volatile metabolites and is considered the most effective among available methods  The volatilomics approach has also been applied in Halal authentication to distinguish among different animal species. The volatile compound profiles can differentiate meat-based products derived from chicken, beef, and pork. While the volatilomics approach shows great potential for use in Halal authentication, additional complementary methods are still required to obtain more comprehensive data.   Keywords: Aroma, Chromatography, Halal, Identification, Vapor, Volatilomics.